At first sight [compact disc, unabridged] - Sparks, Nicholas (Books on Tape, 2005)
Jeremy Marsh is now living in Boone Creek, North Carolina, married to Lexie Darnell, and awaiting the birth of their daughter. But, just as things are looking good, an unsettling and mysterious message brings trouble from the past.